Intimate Partner Violence in the Golden Age: Systematic Review of Risk and Protective Factors - Gerino, Eva; Caldarera, Angela M.; Curti, Lorenzo; Brustia, Piera; Rollè, Luca (Frontiers in Psychology, 2018)
Intimate partner violence (IPV) is identifiable as a major public health concern worldwide. The international literature highlights how this phenomenon is complex and transversal to all age groups. While the global population is becoming older, the scientific research about risk and protective factors related to IPV in the golden age is diverse, and the different findings of the various studies have not been systematized so far. Thus, in this systematic review, we aim to analyze the scientific studies that investigate the risk and the protective factors of violent dynamics between elderly couples. From the perspective of the theoretical frameworks and the methodological approaches used, we present the main conceptual themes that emerge. Following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement, we review the articles that report the analyses of protective and risk factors of IPV perpetration. Our results indicate social support, help-seeking behavior, and the availability of community-based services addressing the issues of abuse as the main protective factors. The risk factors are related to economic conditions, belonging to an ethnic minority, cognitive or physical impairment, other conditions associated with cultural background and relational dynamics, such as intrapartner dependence and intergenerational transmission of violence and trauma, and caregiving stress. We discuss possible future directions of research to improve the understanding of IPV in the elderly population and the implications for the development of intervention policies at preventive and supportive levels.